2023
DOI: 10.55575/tektonika2023.1.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Holocene Earthquakes on the Tambomachay Fault near Cusco, Central Andes

Lorena Rosell

Abstract: A system of active normal faults around the city of Cusco have severely damaged the city in major earthquakes in pre-hispanic times, 1650 and 1950 CE. Detailed studies of these faults adjacent to Cusco are therefore needed to build an understanding of seismic hazard in the region. We present new geomorphological and paleoseismological evidence for multiple Holocene earthquakes on the Tambomachay Fault, a 20 km-long normal fault that runs along the northern margin of the Cusco Basin. The western segment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Besides the existence of fresh scarps and offset moraines that constitute good geomorphological markers (Benavente Escobar et al, 2013;Cabrera et al, 1991;Rosell et al, 2023) and allow us to estimate a current rate of deformation of the order of 1 to 4 mm/year (Wimpenny et al, 2020), palaeoseismic trenches revealed events of moment magnitude (Mw) greater than 6 over the last 10,000 years (Cabrera and Sébrier, 1998;Palomino Tacuri et al, 2021;Rosell et al, 2023). Finally, the installation of a temporary seismological network to the north of Cusco recorded localized seismicity along the Qoricocha and Tambomachay fault planes (Fig.…”
Section: The Cusco Basin a Tectonic-driven Formation Prone To Site Ef...mentioning
confidence: 99%
“…Besides the existence of fresh scarps and offset moraines that constitute good geomorphological markers (Benavente Escobar et al, 2013;Cabrera et al, 1991;Rosell et al, 2023) and allow us to estimate a current rate of deformation of the order of 1 to 4 mm/year (Wimpenny et al, 2020), palaeoseismic trenches revealed events of moment magnitude (Mw) greater than 6 over the last 10,000 years (Cabrera and Sébrier, 1998;Palomino Tacuri et al, 2021;Rosell et al, 2023). Finally, the installation of a temporary seismological network to the north of Cusco recorded localized seismicity along the Qoricocha and Tambomachay fault planes (Fig.…”
Section: The Cusco Basin a Tectonic-driven Formation Prone To Site Ef...mentioning
confidence: 99%